(untitled) (Bangladesh Journal of Animal Science, 2021)
This study was conducted to investigate the morphology, morphometry and production performances of exotic goat breeds and their crossbreds available at Boalia, Shahmokhdum, Rajpara and Matihar thana under Rajshahi metropolitan city. A total of 73 animals’ information was collected from 39 exotic goat flock owners using a semi-structured questionnaire through interviewing of farmers, visual observation and on-spot measurement of the animals. Exotic goat breeds and their crosses were found predominantly higher (>93%) in Rajshahi Metropolitan areas where less than 7% Black Bengal goats were identified. In most cases, deviation of breed specific coat color due to crossing between different types of crossbreds among the populations was noted. The genotype frequencies of Beetal, Kalahari, Sirohi, Jamunapari, Anglo Nubian and their crossbreds and Black Bengal goats were found to be 50.68, 15.07, 13.70, 8.22, 8.22 and 4.11%, respectively. The average mature live weight (12 to 18 months) of those corresponding exotic genotypes in male and female respectively were found 46.88±5.66, 56.07±8.03, 32.67±8.09, 59.54±7.96 and 64.06±4.67 kg, and 21.70±2.24, 22.41±3.64, 17.37±4.05, 24.5±0.5 and 27.47±6.85 kg. Irrespective of genotypes, the mean age at puberty, lactation length, litter size, kidding interval and days open were found 167.50±3.49 days, 76.61±4.90 days, 1.71±0.10, 224.44±5.56 days and 52.64 ± 2.30 days, respectively. However, none of the aforementioned traits differed significantly (P>0.05) among the five different exotic genotypes. In conclusion, this study provides some basic information on the performances of exotic goat breeds or their crossbreds at Metropolitan areas under intensive management conditions which could be utilized for designing proper breeding plan in their conservation and simultaneous improvement. Bang. J. Anim. Sci. 2020. 49 (2): 100-107